NIR‐II AIEgens nanosystem for fluorescence and chemiluminescence synergistic imaging‐guided precise resection in osteosarcoma surgery - Ruotong Li; Kaiyuan Liu; Qian Hu; Jiakang Shen; Dongqing Zuo; Hongsheng Wang; Xingjun Zhu; Wei Sun (Aggregate, 2025)
Abstract Osteosarcoma (OS) is characterized by an unfavorable prognosis and high mortality rates, with the local recurrence attributed to residual lesions post‐surgery being a major reason for treatment failure. Precise and tumor‐specific resection guidance to minimize recurrence remains a significant challenge. In the present study, a nanosystem based on aggregation‐induced emission (AIE) molecules with emission in the second near‐infrared window is proposed for the synergistic fluorescence (FL) and chemiluminescence (CL) imaging‐guided surgical resection for the elimination of tumor foci. The designed AIE molecule, BBTD14, exhibits stable FL with a high quantum yield of up to 3.95%, which effectively matches the energy levels of CL high‐energy states, generating the longest emission wavelength of CL reported to date. Targeted tumor imaging‐guided surgery (IGS) is facilitated by FL and CL nanoprobes (FLNP and CLNP) constructed based on BBTD14. During OS surgery, the FLNP, with the stability of FL and a high targeting capability, was first intravenously used to guide the surgical removal of the main tumor. Subsequently, CLNP was locally incubated to facilitate rapid and accurate evaluation of residual tumors at the operative border. High signal‐to‐noise ratio CL imaging was achieved after spraying with hydrogen peroxide, thereby overcoming the limitations of intraoperative frozen sections. The proposed technique also significantly reduced the recurrence rates in OS mouse models and exhibited high marker specificity in ex vivo OS patient pathology samples, confirming its potential in clinical applications and providing a unique perspective for developing IGS.